Liquid-type lead-acid battery

By using graphite and specific esterification units of negative electrode plate materials in liquid calcium sulfate batteries and controlling the difference in electrode plate distance, the problem of electrolyte density gradient in the battery under partial charging state is solved, and the battery life is improved and the electrolyte reduction is reduced.

JP2025039251APending Publication Date: 2025-03-21GS YUASA CORP

Patent Information

Application Number
JP2023146203
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-08
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Liquid calcium sulfate batteries are prone to electrolyte density gradients in partially charged states, resulting in calcium sulfate accumulation at the bottom of the negative electrode plate, which in turn leads to a decrease in battery capacity and aging of the electrode plate, and shortens battery life.

Method used

The negative plate material containing graphite and specific esterification units is used, and the distance difference between the positive and negative plates is controlled in the battery design so that it is less than or equal to 0.10 mm to reduce the reduction of electrolytes and improve the life of the battery in a partially charged state.

Benefits of technology

By reducing the reduction of electrolytes, the battery's life in a partially charged state is significantly improved and high battery performance is maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025039251000001_ABST
    Figure 2025039251000001_ABST
Patent Text Reader

Abstract

SOLUTION: To provide a liquid-type lead-acid battery including an electrode plate group, an electrolyte, and a cell chamber containing the electrode plates and the electrolyte, the electrode plate group including positive electrode plates, negative electrode plates, and separators interposed between the positive electrode plates and the negative electrode plates, a difference (s-t) between a total s of distances between the positive electrode plates and the negative electrode plates facing each other in the electrode plate group and a total t of thicknesses of the separators being 0.10 mm or less, the positive electrode plates including an element Sb, the negative electrode plate including a negative electrode material, the negative electrode material including graphite and an ester compound having a repeating structure of an oxyalkylene unit, and a content of the ester compound in the negative electrode material being 30 ppm or more based on mass.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to flooded lead-acid batteries. [Background technology]

[0002] Lead-acid batteries are used in a variety of applications, including automotive and industrial use. Lead-acid batteries include negative and positive plates, a separator (or mat), and an electrolyte. Each plate includes a current collector and an electrode material. In order to improve the performance of lead-acid batteries, various attempts have been made, such as improving the separator and using additives in the plates.

[0003] Patent Document 1 discloses a battery comprising a positive electrode plate, a negative electrode plate, and an electrolyte, the positive electrode plate comprising a positive electrode current collector and a positive electrode material, the positive electrode material containing antimony at a content of less than 0.5 mass %, the negative electrode plate comprising a negative electrode material, the negative electrode material containing a polymer compound, the polymer compound being 1 The present invention proposes a lead-acid battery having a peak P1 in the range of 3.2 ppm to 3.8 ppm in the chemical shift of a H-NMR spectrum, and the content of the polymer compound in the negative electrode material is less than 500 ppm by mass.

[0004] Patent Document 2 proposes a lead-acid battery comprising at least one electrode plate group and an electrolyte, the electrode plate group comprising a positive electrode plate, a negative electrode plate, and a separator interposed between the positive electrode plate and the negative electrode plate, the negative electrode plate in the at least one electrode plate group includes a negative electrode material, and the negative electrode material includes an organic shrinkage preventer (excluding a lignin compound) including a monocyclic aromatic compound unit, and the inter-electrode distance between the positive electrode plate and the negative electrode plate is less than 1.1 mm.

[0005] The negative electrode material may contain a carbonaceous material. For example, in the examples and comparative examples of Patent Document 3, lead powder, water, dilute sulfuric acid, barium sulfate, carbon black, graphite, and an organic shrinkage inhibitor (sodium lignin sulfonate) are mixed to prepare a negative electrode paste. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2020 / 241547 [Patent Document 2] International Publication No. 2021 / 060327 [Patent Document 3] JP 2021-170429 A (paragraph

[0053] ) Summary of the Invention [Problem to be solved by the invention]

[0007] Flooded lead-acid batteries are sometimes used in a state of insufficient charge called a partial state of charge (PSOC). When a lead-acid battery is used in PSOC, stratification tends to progress, in which the electrolyte density at the top of the battery is gradually lower and that at the bottom of the battery is gradually higher. As stratification progresses, accumulation of lead sulfate becomes prominent at the bottom of the negative plate, and sulfation, in which lead sulfate crystals form, tends to occur. This leads to a decrease in capacity and uneven charge / discharge reactions that deteriorate the plate, shortening the life of the lead-acid battery. For example, high life performance in PSOC is required for idling stop applications. Hereinafter, life performance in PSOC may be referred to as PSOC life performance.

[0008] When the negative electrode material contains graphite or the positive electrode plate contains Sb, a high PSOC life performance is easily obtained. However, in either case, there is a tradeoff in that the amount of electrolyte decrease becomes significant. [Means for solving the problem]

[0009] One aspect of the present disclosure is a flooded lead-acid battery, The flooded lead-acid battery includes a plate group, an electrolyte, and a cell chamber that accommodates the plate group and the electrolyte, the electrode plate group includes a positive electrode plate, a negative electrode plate, and a separator interposed between the positive electrode plate and the negative electrode plate, The difference (st) between the total distance s between the positive electrode plates and the negative electrode plates facing each other in the electrode plate group and the total thickness t of the separator is 0.10 mm or less, The positive electrode plate contains Sb element, The negative electrode plate includes a negative electrode material, The negative electrode material contains graphite and an ester compound having a repeating structure of oxyalkylene units, the content of the ester compound in the negative electrode material is 30 ppm or more by mass. Effect of the Invention

[0010] In flooded lead-acid batteries, this can ensure high PSOC life performance while reducing the amount of electrolyte loss. [Brief description of the drawings]

[0011] [Figure 1] 1 is a partially cutaway exploded perspective view illustrating the outer appearance and internal structure of a flooded lead-acid battery according to one aspect of the present invention. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Graphite is less likely to leak into the electrolyte than carbon black, so the conductive network is more likely to be maintained in negative plates containing graphite. Therefore, flooded lead-acid batteries using negative plates containing graphite can achieve relatively high PSOC life performance. However, negative plates containing graphite are more likely to cause side reactions involving the electrolyte, which generates a lot of gas and reduces the electrolyte.

[0013] On the other hand, when a positive electrode plate containing Sb is used, the Sb element suppresses the softening and falling off of the positive electrode material, improving the PSOC life performance. However, Sb eluted from the positive electrode plate is deposited on the negative electrode plate, lowering the hydrogen generation overvoltage of the negative electrode plate. This increases the amount of hydrogen gas generated in the negative electrode plate, making it easier for the electrolyte to decrease.

[0014] When a negative electrode plate containing graphite is combined with a positive electrode plate containing Sb, a high PSOC life performance is obtained. However, it has become clear that such a combination may cause a further decrease in electrolyte than would be expected from the use of a negative electrode plate containing graphite and a positive electrode plate containing Sb. Hereinafter, the decrease in electrolyte is sometimes referred to as "loss of electrolyte," and the amount of electrolyte loss is sometimes referred to as "amount of electrolyte loss."

[0015] In view of the above, (1) a flooded lead-acid battery according to one aspect of the present invention includes a plate assembly, an electrolyte, and a cell chamber that accommodates the plate assembly and the electrolyte. The plate assembly includes a positive plate, a negative plate, and a separator interposed between the positive plate and the negative plate. The difference (st) between the total distance s between the positive plate and the negative plate facing each other in the plate assembly and the total thickness t of the separator is 0.10 mm or less. The positive plate includes antimony (Sb). The negative plate includes a negative electrode material. The negative electrode material includes graphite and an ester compound having a repeating structure of oxyalkylene units. The content of the ester compound in the negative electrode material is 30 ppm or more by mass. The ester compound having a repeating structure of oxyalkylene units may be simply referred to as an "ester compound" or a "specific ester compound" below. The flooded lead-acid battery may also be called a vented lead-acid battery.

[0016] In one aspect of the present invention, the flooded lead-acid battery satisfies (st)≦0.10 mm, and the negative electrode material contains a specific ester compound. This makes it possible to reduce the amount of electrolyte loss when a negative electrode plate containing graphite is combined with a positive electrode plate containing Sb. By combining such a negative electrode plate and a positive electrode plate, it is possible to ensure high PSOC life performance.

[0017] When (st)>0.10mm, a combination of a negative plate containing graphite and an ester compound with a positive plate containing Sb element can provide a relatively high PSOC life performance. However, in these combinations, the amount of liquid loss is greater than expected from the effects of graphite, ester compound, and Sb element on the liquid loss. When (st)≦0.10mm, the tendency of the effects of graphite, ester compound, and Sb element on the liquid loss is almost the same as when (st)>0.10mm. However, in reality, in the flooded lead-acid battery according to one aspect of the present invention with (st)≦0.10mm, the amount of liquid loss is greatly reduced compared to the effect of each component. Thus, the tendency of liquid loss when a negative plate containing graphite and an ester compound is combined with a positive plate containing Sb element is significantly different between when (st)>0.10mm and when (st)≦0.10mm.

[0018] Furthermore, in the flooded lead-acid battery according to one aspect of the present invention, the PSOC life performance is significantly improved compared to when (st)>0.10 mm, or when (st)≦0.10 mm and some components are used. Ester compounds have a repeating structure of oxyalkylene units. However, unlike ester compounds, polyethylene glycol or polypropylene glycol, which has a repeating structure of oxyalkylene units, has a small effect of suppressing liquid loss. Therefore, in order to obtain a sufficient effect of suppressing liquid loss while ensuring high PSOC life performance, it is important to use a specific ester compound.

[0019] In order to obtain a sufficient effect of suppressing the loss of electrolyte due to the ester compound, the negative electrode material needs to contain a certain amount of the ester compound. From this viewpoint, the content of the ester compound in the negative electrode material is 30 ppm or more by mass.

[0020] In the flooded lead-acid battery according to one aspect of the present invention, the amount of electrolyte loss is reduced due to the following (a) and (b). (a) When (st)<0.10 mm and the negative electrode material contains a specific ester compound, a gas absorption reaction occurs even though the battery is a flooded lead-acid battery. (b) By combining a negative plate containing a specific ester compound and graphite with a positive plate containing Sb element, the amount of hydrogen gas generated in the negative plate is reduced.

[0021] Regarding (b) above, Sb dissolves from the positive plate and deposits on the negative plate. As a result, the hydrogen generation overvoltage in the negative plate decreases, making it easier for hydrogen gas to be generated. Graphite has high hydrogen generation activity at the edge. Since the combination of graphite and Sb increases the amount of liquid loss more than would be expected from each alone, it is believed that Sb is adsorbed and interacts with the edge of the graphite in the negative plate, resulting in a large amount of hydrogen gas generation. However, if an ester compound is included in the negative electrode material, it is believed that the surface of the graphite is coated with the ester compound. As a result, it is believed that the interaction between graphite and Sb is reduced, thereby reducing the amount of hydrogen gas generated.

[0022] In addition, by setting (st)≦0.10 mm in the above (a), the space between the plates is more sealed, and oxygen generated in the positive plate is less likely to be released to the outside of the space between the plates. This increases the oxygen concentration in the space, and oxygen is efficiently supplied to the negative plate. It is believed that the increase in oxygen concentration near the negative plate and the decrease in hydrogen concentration balance the oxygen and hydrogen, and the gas absorption reaction occurs even in the liquid battery.

[0023] When (st)≦0.10 mm, the space between the plates is narrower and more closed than when (st)>0.10 mm. When the space between the plates becomes relatively small, as in this case, the closedness of the space is said to be relatively increased. It is believed that the lead-acid battery according to one aspect of the present invention is a liquid type battery, and thus a gas absorption reaction occurs.

[0024] In the flooded lead-acid battery according to one aspect of the present invention, high PSOC life performance is obtained. This is believed to be due to the following reasons. First, it is believed that the Sb element suppresses the softening and falling off of the positive electrode material. In addition, since the negative electrode material contains graphite, a high conductive network is maintained in the negative electrode plate. In addition, it is believed that Sb eluted from the positive electrode plate is precipitated on the negative electrode plate, further improving the conductivity of the negative electrode plate. It is believed that the accumulation of lead sulfate is suppressed by obtaining high conductivity in the negative electrode plate.

[0025] (2) In the above (1), the content of the ester compound in the negative electrode material may be 220 ppm or less by mass, thereby achieving even higher PSOC life performance.

[0026] (3) In the above (1) or (2), the repeating structure of the oxyalkylene unit in the ester compound may contain a repeating structure of an oxyethylene unit. In this case, the hydrophilicity and hydrophobicity of the ester compound are balanced, and the graphite is easily coated, so that the liquid loss is further suppressed.

[0027] (4) In any one of the above (1) to (3), the graphite content in the negative electrode material may be 0.3 mass% or more and 2.5 mass% or less, which can further suppress loss of electrolyte and achieve higher PSOC life performance.

[0028] (5) In any one of the above (1) to (4), the positive electrode plate may contain Sb element. The content of Sb element in the positive electrode material may be 0.01 mass% or more and 0.20 mass% or less. In this case, the loss of the electrolyte can be further suppressed and a higher PSOC life performance can be obtained.

[0029] (6) In any one of the above (1) to (5), in a cross section of the flooded lead-acid battery parallel to the bottom of the cell chamber, the ratio Ra (=Se / Sg=(S1-Sg) / Sg) of the area (Se) obtained by subtracting the cross-sectional area (Sg) of the plate group from the cross-sectional area (S1) inside the cell chamber to the cross-sectional area (Sg) of the plate group may be 0.20 or less. In this case, the amount of electrolyte loss can be further reduced. The area (=Se=S1-Sg) obtained by subtracting the cross-sectional area of ​​the plate group from the cross-sectional area inside the cell chamber corresponds to the cross-sectional area of ​​the electrolyte present outside the outer edge of the plate group (outside the plate group) in the above cross section (in other words, the electrolyte surrounding the plate group in the cell chamber in which the plate group is accommodated). Therefore, it can be said that when Ra≦0.20, the amount of electrolyte present outside the plate group is smaller than when Ra>0.20. When Ra≦0.20, the amount of oxygen generated in the positive plate that migrates to the electrolyte outside the electrode assembly is smaller than when Ra>0.20, so a high concentration of oxygen can be retained between the electrodes. Therefore, when Ra≦0.20, more oxygen is supplied to the negative plate than when Ra>0.20, so it is thought that the gas absorption reaction occurs more easily. In addition, when Ra≦0.20, the PSOC life performance is significantly improved compared to when Ra>0.20. This is thought to be because the relatively small amount of electrolyte outside the electrode assembly suppresses stratification and deterioration of the electrode plates.

[0030] The flooded lead-acid battery according to one aspect of the present invention will be described in more detail below, including the above (1) to (6). At least one selected from the components described below, including the description of the embodiments and examples, can be arbitrarily combined with at least one of the above (1) to (6) for the flooded lead-acid battery according to one aspect of the present invention, as long as such combination is technically possible.

[0031] [Liquid lead acid battery] The flooded lead-acid battery may include at least one cell. The cell includes a plate assembly, an electrolyte, and a cell chamber that contains the plate assembly and the electrolyte. The plate assembly includes a positive electrode plate, a negative electrode plate, and a separator interposed between the positive electrode plate and the negative electrode plate.

[0032] In a flooded lead-acid battery according to one aspect of the present invention, the difference (st) is 0.10 mm or less. When the difference (st) is so small, by combining a positive electrode plate containing Sb element with a negative electrode plate whose negative electrode material contains graphite and 30 mass ppm or more of a specific ester compound, it is possible to reduce the amount of liquid loss while ensuring high PSOC life performance. From the viewpoint of further reducing the amount of liquid loss and further improving the PSOC life performance, the difference (st) may be 0.07 mm or less, 0.05 mm or less, or may be 0.00 mm or less. From the viewpoint of reducing permeation short circuit and suppressing stratification, the difference (st) may be, for example, -0.15 mm or more, or -0.10 mm or more.

[0033] The difference (st) may be -0.15 mm or more (or -0.10 mm or more) and 0.10 mm or less, -0.15 mm or more (or -0.10 mm or more) and 0.07 mm or less, -0.15 mm or more (or -0.10 mm or more) and 0.05 mm or less, or -0.15 mm or more (or -0.10 mm or more) and 0.00 mm or less.

[0034] (Measurement of difference (st)) The difference (st) is measured using a plate group taken out of a fully charged lead-acid battery. The total distance s between the opposing positive and negative plates in the plate group is the length between the outer surfaces of the plates at both ends in the direction parallel to the stacking direction of the plate group minus the total thickness of the positive and negative plates, divided by (number of plates - 1) (unit: mm).

[0035] The thickness of each of the positive and negative plates is determined by the following procedure: Remove all positive and negative plates from the plate group. Measure the thickness of all positive plates in the plate group with a vernier caliper and average the thickness to determine the thickness of the positive plates. In a lead-acid battery with multiple plate groups, measure the thickness of the positive plates in one plate group located at the end and one plate group located near the center and average the thickness to determine the thickness (average value) of the positive plates. The thickness of the negative plates is determined in the same manner as for the positive plates.

[0036] The total thickness t of the separators in the electrode plate group is the total value (unit: mm) obtained by measuring the thickness of all the separators present between adjacent positive and negative plates in the electrode plate group. The thickness of the separator is measured with a vernier caliper. If the separator has ribs in the portion facing the electrode material, the thickness of the separator is measured in the portion where the ribs are present. If the separator has ribs (first rib, second rib) on both surfaces of the base portion and the base portion, and the positions of the ribs (the positions of the first rib and the second rib) are misaligned on both surfaces, the vernier caliper is used to measure the sum s1 of the thickness of the base portion and the height of the first rib in the portion of the rib (first rib) on one surface, and the sum s2 of the thickness of the base portion and the height of the second rib in the portion of the rib (second rib) on the other surface, and the thickness t of only the base portion is measured. b Measure s1+s2-t b The thickness of the separator is determined by measuring the thickness at multiple locations (for example, five locations) of the electrode plate assembly and averaging the measurements.

[0037] A separator sample for measurement (Sample A) is prepared by removing the sulfuric acid from a separator removed from a fully charged lead-acid battery by rinsing with water. The size of the separator is measured while the separator is wet with water within 10 minutes after rinsing.

[0038] If the battery includes a plurality of electrode plate groups, s and t are obtained for one of the outermost electrode plate groups and one of the electrode plate groups near the center, and st is calculated.

[0039] In the flooded lead-acid battery, the plate group may include a plurality of positive electrodes, a plurality of negative electrodes, and a separator interposed between the positive electrodes and the negative electrodes. The positive electrodes and negative electrodes are alternately stacked with the separator interposed therebetween. The width direction of the plate group (hereinafter referred to as the "x direction") is a direction perpendicular to the stacking direction of the positive electrodes, negative electrodes, and separators (hereinafter referred to as the "y direction") and perpendicular to the up-down direction (vertical direction). The up-down direction (vertical direction) is defined as the z direction. Each direction is based on the arrangement direction of the lead-acid battery when in use.

[0040] A flooded lead-acid battery usually includes a battery case. The battery case has a bottom, a side wall rising from the periphery of the bottom, and a lid that closes the open end of the side wall. The inside of the battery case may be divided into a plurality of spaces (cell chambers) by partition walls. The inside of the battery case may be divided into a plurality of spaces (e.g., six) by partition walls that are parallel to each other. The interior of the battery case may be divided into a plurality of spaces (e.g., four or more) by a plurality of partition walls that cross each other. When the battery case is not divided into a plurality of cell chambers or does not have a cell chamber, the battery case is regarded as one cell chamber. Each cell chamber is formed, for example, such that the dimension X in the x direction (width direction of the electrode plate group) is larger than the dimension (group length) Y in the y direction (stacking direction) of the electrode plate group.

[0041] The components of the flooded lead-acid battery will be described in more detail below.

[0042] (Positive plate) The positive electrode plate may be, for example, a paste-type positive electrode plate, which includes, for example, a positive electrode current collector and a positive electrode material.

[0043] The positive electrode current collector may be formed by casting lead (Pb) or a lead alloy, or may be formed by processing a lead sheet or a lead alloy sheet. Examples of the processing method include expanding and punching. It is preferable to use a lattice-shaped current collector as the positive electrode current collector because it is easy to support the positive electrode material.

[0044] As the lead alloy used for the positive electrode current collector, in terms of corrosion resistance and mechanical strength, Pb-Sb alloy, Pb-Ca alloy, Pb-Ca-Sn alloy are preferable. The positive electrode current collector may have a surface layer. The surface layer and the inner layer of the positive electrode current collector may have different compositions. The surface layer may be formed so as to cover the entire positive electrode current collector, or may be formed on a part of the positive electrode current collector. The surface layer may be formed only on the lattice part, the lug part, or the frame part of the positive electrode current collector.

[0045] The positive electrode material contained in the positive electrode plate usually contains a positive electrode active material (lead dioxide or lead sulfate) that develops capacity through an oxidation-reduction reaction. The positive electrode material may contain other additives as necessary.

[0046] The positive electrode plate contains an Sb element. The Sb element is contained in at least one selected from the group consisting of a positive electrode material and a positive electrode current collector (including the surface layer). When the positive electrode plate contains the Sb element, the softening and falling off of the positive electrode material is suppressed. In addition, Sb eluted from the positive electrode plate is precipitated on the negative electrode plate, improving the conductivity of the negative electrode plate. Thus, high PSOC life performance is obtained. From the viewpoint of further suppressing the softening and falling off of the positive electrode material, it is preferable that the Sb element is contained at least in the positive electrode material. In addition to the positive electrode plate, the Sb element may be contained in a positive electrode strap connecting multiple positive electrode plates.

[0047] There are no particular limitations on the form in which the Sb element is contained in the positive electrode material, and the Sb element may be contained in the form of, for example, an Sb compound, an Sb metal, an Sb alloy, an Sb ion, or the like.

[0048] The content of Sb element in the positive electrode plate may be 0.01 mass% or more. When the content of Sb element is in such a range, high PSOC life performance is obtained. From the viewpoint of ensuring higher PSOC life performance, the content of Sb element in the positive electrode plate is preferably 0.03 mass% or more, and more preferably 0.05 mass% or more. From the viewpoint of further suppressing the loss of the electrolyte, the content of Sb element in the positive electrode plate may be 0.20 mass% or less, 0.13 mass% or less, or 0.10 mass% or less.

[0049] The content of Sb element in the positive electrode plate may be 0.01 mass% or more (or 0.03 mass% or more) and 0.20 mass% or less, 0.01 mass% or more (or 0.03 mass% or more) and 0.13 mass% or less, 0.01 mass% or more (or 0.03 mass% or more) and 0.10 mass% or less, 0.05 mass% or more and 0.20 mass% or less (or 0.13 mass% or less), or 0.05 mass% or more and 0.10 mass% or less.

[0050] When the positive electrode material contains Sb element, the content of Sb element in the positive electrode material may be 0.01 mass% or more. When the content of Sb element is in such a range, high PSOC life performance is obtained. From the viewpoint of ensuring higher PSOC life performance, the content of Sb element in the positive electrode material is preferably 0.03 mass% or more, more preferably 0.05 mass% or more. From the viewpoint of further suppressing the loss of the liquid, the content of Sb element in the positive electrode material may be 0.20 mass% or less, 0.13 mass% or less, or 0.10 mass% or less.

[0051] The content of Sb element in the positive electrode material may be 0.01 mass% or more (or 0.03 mass% or more) and 0.20 mass% or less, 0.01 mass% or more (or 0.03 mass% or more) and 0.13 mass% or less, 0.01 mass% or more (or 0.03 mass% or more) and 0.10 mass% or less, 0.05 mass% or more and 0.20 mass% or less (or 0.13 mass% or less), or 0.05 mass% or more and 0.10 mass% or less.

[0052] An unformed paste-type positive electrode plate is obtained by filling a positive electrode current collector with a positive electrode paste, aging, and drying. The positive electrode paste is prepared by kneading lead powder, additives (reinforcing materials (e.g., resin fibers), water, and sulfuric acid. The positive electrode paste may contain an antimony compound. Examples of antimony compounds include oxides (antimony trioxide, etc.). A positive electrode plate is obtained by forming the unformed positive electrode plate.

[0053] The formation of the unformed positive plate may be carried out, for example, by placing a plate assembly including the unformed positive plate and an electrolyte containing sulfuric acid in a lead-acid battery container, and charging the plate assembly in a state in which the electrolyte permeates the plate assembly. However, the formation may also be carried out before assembling the lead-acid battery or the plate assembly.

[0054] (Analysis or measurement of positive plate or positive electrode material) (Sample preparation) The analysis or measurement is performed on a positive plate taken from a fully charged lead-acid battery. The sample for analysis or measurement is prepared in the following manner. First, a fully charged lead-acid battery is disassembled to obtain a positive plate to be analyzed. The obtained positive plate is washed with water to remove sulfuric acid from the positive plate. The washing is continued until a pH test paper is pressed against the washed surface of the positive plate and no change in color is confirmed. The washed positive plate is dried in a thermostatic chamber at 50°C ± 2°C for 12 hours or more. After drying, if the positive plate contains an adhesive material, the adhesive material is removed from the positive plate by peeling. The mass of the dried material (positive plate) is measured. In this manner, a positive plate is obtained.

[0055] Next, for the dried product (positive electrode plate), the positive electrode material is dropped from the positive electrode current collector to obtain a sample of the positive electrode material.

[0056] After the positive electrode material is removed, the positive electrode material adhering to the positive electrode collector is removed by a mannite treatment. The resulting positive electrode collector is washed with water and dried to obtain a sample of the positive electrode collector. After drying, the mass of the positive electrode collector is measured. The mass of the positive electrode material contained in the positive electrode plate is calculated by subtracting the mass of the positive electrode collector from the mass of the positive electrode plate.

[0057] (Quantitative analysis of Sb element) (Sb element content in positive electrode material) An appropriate amount of sample of the positive electrode material is taken and its mass is measured. Next, the entire amount of the sample is dissolved in a mixed aqueous solution containing tartaric acid, nitric acid, and hydrogen peroxide. The solution obtained by dissolving the entire amount is diluted with ion-exchanged water as necessary to a constant volume, and then the emission intensity of Sb in the solution is measured by high-frequency inductively coupled plasma (ICP) emission spectroscopy. Then, the mass of Sb contained in the solution is calculated using a calibration curve prepared in advance. The ratio (mass%) of the Sb mass to the mass of the sample of the positive electrode material used for analysis is calculated as the content of Sb element in the positive electrode material.

[0058] (Sb content in positive electrode plate) The content (mass%) of the Sb element is obtained using a sample of the positive electrode current collector. More specifically, a part of the sample of the positive electrode current collector is taken to prepare a sample for analysis. More specifically, a part of the positive electrode current collector is cut perpendicular to the surface direction using a ceramic knife. After measuring the mass of the taken sample, the entire amount of the sample is dissolved by mixing with tartaric acid and dilute nitric acid. The obtained solution is diluted with ion-exchanged water as necessary to a constant volume, and the emission intensity of Sb in the solution is measured by ICP emission spectroscopy. Then, the Sb concentration in the filtrate is obtained using a calibration curve prepared in advance. The content (mass%) of the Sb element in the positive electrode current collector is obtained from the Sb concentration and the mass of the analysis sample of the positive electrode current collector provided for analysis.

[0059] The content (mass%) of Sb element in the positive plate is calculated from the mass ratio of the positive electrode material and the positive electrode current collector in the positive plate, the content of Sb element in the positive electrode material, and the content of Sb element in the positive electrode current collector. The ICP optical emission spectrometer used is ICPS-8000 manufactured by Shimadzu Corporation.

[0060] (Negative plate) The negative plate includes a negative electrode material and typically includes a negative current collector.

[0061] The negative electrode current collector may be formed by casting lead (Pb) or a lead alloy, or may be formed by processing a lead sheet or a lead alloy sheet. Examples of the processing method include expanding and punching. It is preferable to use a lattice-shaped current collector as the negative electrode current collector because it is easy to support the negative electrode material.

[0062] The lead alloy used for the negative electrode current collector may be any of Pb-Sb alloy, Pb-Ca alloy, and Pb-Ca-Sn alloy. These lead or lead alloys may further contain at least one element selected from the group consisting of Ba, Ag, Al, Bi, As, Se, Cu, etc., as an additive element.

[0063] The negative electrode current collector may have a surface layer. The surface layer and the inner layer of the negative electrode current collector may have different compositions. The surface layer may be formed so as to cover the entire negative electrode current collector, or may be formed on a part of the negative electrode current collector. The surface layer may be formed, for example, only on the lattice portion, only on the edge portion, or only on the frame portion of the negative electrode current collector.

[0064] The negative electrode material includes graphite and a specific ester compound. The negative electrode material includes a negative electrode active material (lead or lead sulfate) that exhibits capacity through an oxidation-reduction reaction. The negative electrode material may include additives other than graphite and the specific ester compound, as necessary. Examples of additives include an organic shrinkage inhibitor, a carbonaceous material other than graphite, and barium sulfate. The negative electrode material may include a reinforcing material (such as resin fiber) in addition to these additives. Graphite may be referred to as a first carbonaceous material, and a carbonaceous material other than graphite may be referred to as a second carbonaceous material.

[0065] (graphite) The negative electrode material includes graphite (first carbonaceous material). Graphite is a carbonaceous material that includes a graphite-type crystal structure. In this specification, -1 More than 1350cm -1 Peaks appearing in the following range (D band) and 1550 cm -1 More than 1600cm -1 Intensity ratio I to the peak (G band) appearing in the following range D / I G A carbonaceous material having a γ of 0 or more and 0.9 or less is called graphite. Graphite may be either artificial graphite or natural graphite. The negative electrode material may contain one type of graphite or a combination of two or more types of graphite.

[0066] The graphite content in the negative electrode material may be 0.1% by mass or more, or may be 0.2% by mass or more. From the viewpoint of easily obtaining a higher PSOC life performance, the graphite content in the negative electrode material is preferably 0.3% by mass or more, and more preferably 0.5% by mass or more. The graphite content in the negative electrode material may be 2.5% by mass or less. From the viewpoint of further suppressing the loss of the liquid, the graphite content in the negative electrode material is preferably 2.0% by mass or less, and more preferably 1.7% by mass or less or 1.5% by mass or less.

[0067] The graphite content in the negative electrode material may be 0.1 mass% or more (or 0.2 mass% or more) and 2.5 mass% or less, 0.1 mass% or more (or 0.2 mass% or more) and 2.0 mass% or less, 0.1 mass% or more (or 0.2 mass% or more) and 1.7 mass% or less, 0.1 mass% or more (or 0.2 mass% or more) and 1.5 mass% or less, 0.3 mass% or more (or 0.5 mass% or more) and 2.5 mass% or less, 0.3 mass% or more (or 0.5 mass% or more) and 2.0 mass% or less, 0.3 mass% or more (or 0.5 mass% or more) and 1.7 mass% or less, or 0.3 mass% or more (or 0.5 mass% or more) and 1.5 mass% or less.

[0068] In the negative electrode material, the mass ratio of graphite to the total of the graphite and the second carbonaceous material may be 50 mass% or more, 75 mass% or more, or 85 mass% or more. The mass ratio of graphite is 100 mass% or less.

[0069] (Second carbonaceous material) The negative electrode material may contain a second carbonaceous material. Examples of the second carbonaceous material include carbon black, hard carbon, and soft carbon. Examples of carbon black include acetylene black, furnace black, and lamp black. Furnace black also includes Ketjen Black (trade name). The negative electrode material may contain one type of the second carbonaceous material, or may contain two or more types.

[0070] (Ester compounds) The ester compound has a repeating structure of an oxyalkylene unit. Examples of the oxyalkylene unit include an oxyethylene unit, an oxypropylene unit, an oxytrimethylene unit, an oxy2-methyl-1,3-propylene unit, an oxy1,4-butylene unit, and an oxy1,3-butylene unit. Examples of the oxyalkylene unit include an oxyC 2-4 It may be an alkylene unit (oxyethylene unit, oxypropylene unit, etc.). 2-4 The ester compound having an alkylene unit is 1 In the H-NMR spectrum, it has a peak in the range of 3.2 ppm to 3.8 ppm.

[0071] The repeating structure may contain one type of oxyalkylene unit, or may contain two or more types of oxyalkylene units. The ester compound may contain one type of the repeating structure, or may contain two or more types of the repeating structures. From the viewpoint of easily reducing the interaction between graphite and Sb by adhering to the graphite surface, the repeating structure of the oxyalkylene unit preferably contains a repeating structure of an oxyethylene unit. The ester compound may contain a repeating structure of an oxyethylene unit and another oxyalkylene unit (a repeating structure of another oxyalkylene unit). The ester compound having a repeating structure of an oxyalkylene unit also includes ester compounds classified as surfactants (more specifically, nonionic surfactants).

[0072] Examples of the ester compound include esters of hydroxy compounds having a repeating structure of oxyalkylene units (polyalkylene glycols, copolymers containing a repeating structure of oxyalkylene, polyalkylene oxide adducts of polyols, etc.).

[0073] As copolymers, different oxy C 2-4 Copolymers containing alkylene units, etc. The copolymer may be a block copolymer.

[0074] The polyol may be any of aliphatic polyols, alicyclic polyols, aromatic polyols, and heterocyclic polyols. From the viewpoint that the ester compound is likely to spread thinly on the surface of lead or graphite, aliphatic polyols and alicyclic polyols (e.g., polyhydroxycyclohexane, polyhydroxynorbornane) are preferred, and among them, aliphatic polyols are preferred. Examples of aliphatic polyols include aliphatic diols and polyols having a triol or more (e.g., glycerin, trimethylolpropane, pentaerythritol, sugar, or sugar alcohol). Examples of aliphatic diols include alkylene glycols having 5 or more carbon atoms. Examples of alkylene glycols include C 5-14 Alkylene glycol or C 5-10 The polyol may be an alkylene glycol. Examples of sugars or sugar alcohols include sucrose, erythritol, xylitol, mannitol, and sorbitol. The sugar or sugar alcohol may have either a chain structure or a cyclic structure. In the polyalkylene oxide adduct of the polyol, the alkylene oxide corresponds to the oxyalkylene unit of the ester compound. From the viewpoint of facilitating thin adhesion of the ester compound to the lead surface or graphite surface, the polyol is preferably a diol.

[0075] The esterified product is a hydroxy compound having a repeating structure of oxyalkylene units, in which at least some of the terminal -OH groups (-OH groups consisting of a hydrogen atom of the terminal group and an oxygen atom bonded to this hydrogen atom) are esterified to form -OC(=O)-R 1 Groups, where R 1 is an organic group.) Of the terminals of the hydroxy compound, some terminals may be esterified, or all terminals may be esterified. For example, one terminal of the main chain of a linear ester compound is an -OH group and the other terminal is an -OC(=O)-R 1 It may also be a group.

[0076] organic group R 1Examples of the substituent include a hydrocarbon group. The hydrocarbon group may have a substituent (e.g., a hydroxy group, an alkoxy group, and / or a carboxy group). The hydrocarbon group may be any of aliphatic, alicyclic, and aromatic. The aromatic hydrocarbon group and the alicyclic hydrocarbon group may have an aliphatic hydrocarbon group (e.g., an alkyl group, an alkenyl group, an alkynyl group) as a substituent. The number of carbon atoms in the aliphatic hydrocarbon group as a substituent may be, for example, 1 to 30, 1 to 20, 1 to 10, 1 to 6, or 1 to 4.

[0077] Examples of aromatic hydrocarbon groups include aromatic hydrocarbon groups having 24 or less carbon atoms. The number of carbon atoms in the aromatic hydrocarbon group may be 20 or less, or may be 12 or less. The number of carbon atoms in the aromatic hydrocarbon group may be 6 or more. Examples of aromatic hydrocarbon groups include aryl groups, bisaryl groups, and the like. Examples of aryl groups include phenyl groups and naphthyl groups. Examples of bisaryl groups include monovalent groups corresponding to bisarenes. Examples of bisarenes include biphenyl, bisarylalkanes (e.g., bisC 6-10 Aryl C 1-4 Alkanes (such as 2,2-bisphenylpropane) are examples.

[0078] Examples of the alicyclic hydrocarbon group include alicyclic hydrocarbon groups having 16 or less carbon atoms. The alicyclic hydrocarbon group may be a cross-linked cyclic hydrocarbon group. The number of carbon atoms in the alicyclic hydrocarbon group may be 10 or less or 8 or less. The number of carbon atoms in the alicyclic hydrocarbon group may be, for example, 5 or more.

[0079] Examples of alicyclic hydrocarbon groups include cycloalkyl groups (cyclopentyl, cyclohexyl, cyclooctyl, etc.) and cycloalkenyl groups (cyclohexenyl, cyclooctenyl, etc.). Alicyclic hydrocarbon groups also include hydrogenated products of the above aromatic hydrocarbon groups.

[0080] From the viewpoint of facilitating thin adhesion of the ester compound to the lead or graphite surface, among the hydrocarbon groups, an aliphatic hydrocarbon group is preferred. The aliphatic hydrocarbon group may be saturated or unsaturated. Examples of the aliphatic hydrocarbon group include an alkyl group, an alkenyl group, an alkynyl group, a dienyl group having two carbon-carbon double bonds, and a trienyl group having three carbon-carbon double bonds. The aliphatic hydrocarbon group may be either linear or branched.

[0081] The number of carbon atoms in the aliphatic hydrocarbon group is, for example, 30 or less, and may be 22 or less, or may be 18 or less. The lower limit of the number of carbon atoms depends on the type of the aliphatic hydrocarbon group; for alkyl groups, it is 1 or more, for alkenyl groups and alkynyl groups, it is 2 or more, for dienyl groups, it is 3 or more, and for trienyl groups, it is 4 or more. Among them, from the viewpoint of facilitating a thin adhesion of the ester compound to the surface of lead or graphite, alkyl groups and alkenyl groups are preferred.

[0082] Specific examples of the alkyl group include methyl, ethyl, n-propyl, i-propyl, n-butyl, i-butyl, s-butyl, t-butyl, n-pentyl, neopentyl, i-pentyl, s-pentyl, 3-pentyl, t-pentyl, n-hexyl, 2-ethylhexyl, n-octyl, n-nonyl, n-decyl, i-decyl, undecyl, lauryl (dodecyl), tridecyl, myristyl, pentadecyl, cetyl, heptadecyl, stearyl, icosyl, henicosyl, and behenyl. 1-30 may be an alkyl group, 1-22 may be an alkyl group, 10-18 It may be an alkyl group.

[0083] Specific examples of the alkenyl group include vinyl, 1-propenyl, allyl, cis-9-heptadecen-1-yl, palmitoleyl, and oleyl. 2-30 may be an alkenyl group, C 2-22 may be an alkenyl group, C 10-18 It may be an alkenyl group.

[0084] The ester compound may have one or more hydrophobic groups. Examples of the hydrophobic group include, among the above-mentioned hydrocarbon groups, aromatic hydrocarbon groups, alicyclic hydrocarbon groups, and long-chain aliphatic hydrocarbon groups. Examples of the long-chain aliphatic hydrocarbon group include, among the above-mentioned aliphatic hydrocarbon groups (alkyl groups, alkenyl groups, etc.), aliphatic hydrocarbon groups having 8 or more carbon atoms. The carbon number of the aliphatic hydrocarbon group is preferably 10 or more, more preferably 12 or more. The ester compound may be an ester compound in which at least one of the hydrophobic groups is a long-chain aliphatic hydrocarbon group. The carbon number of the long-chain aliphatic hydrocarbon group may be 30 or less, 22 or less, or 18 or less.

[0085] The number of carbon atoms in the long-chain aliphatic hydrocarbon group may be 8 or more (or 10 or more) and 30 or less, 8 or more (or 10 or more) and 22 or less, 8 or more (or 10 or more) and 18 or less, 12 or more and 30 or less (or 22 or less), or 12 or more and 18 or less.

[0086] Among ester compounds, ester compounds having a hydrophilic group and a hydrophobic group correspond to nonionic surfactants. The repeating structure of an oxyethylene unit exhibits high hydrophilicity and can become a hydrophilic group in a nonionic surfactant. Therefore, it is preferable that the ester compound having the above-mentioned hydrophobic group contains a repeating structure of an oxyethylene unit. Such an ester compound can adsorb to lead and graphite in a well-balanced manner due to the balance between hydrophobicity and high hydrophilicity due to the repeating structure of the oxyethylene unit, while suppressing excessive coverage of the lead surface, so that the generation of hydrogen gas can be reduced and the efficiency of the gas absorption reaction can be improved. Such an ester compound can ensure high adsorption to lead and graphite even if it has a relatively low molecular weight (for example, a number average molecular weight Mn of 1000 or less).

[0087] Examples of ester compounds having a hydrophobic group and a repeating structure of oxyethylene units include esters of polyethylene glycol (such as carboxylic acid esters) and esters of polyethylene oxide adducts of the above polyols (such as triols or higher polyols). The use of such ester compounds is advantageous because it is easy to ensure higher PSOC life performance and can further suppress loss of liquid. Specific examples of such ester compounds include, but are not limited to, polyethylene glycol oleate, polyethylene glycol dioleate, polyethylene glycol dilaurate, polyethylene glycol distearate, polyoxyethylene coconut oil fatty acid sorbitan, polyoxyethylene sorbitan oleate, and polyoxyethylene sorbitan stearate.

[0088] From the viewpoint of being able to thinly cover lead and graphite with high adsorptivity, ester compounds are preferred. 2-4 It is preferable that the ester compound contains a large amount of alkylene units. Such an ester compound contains, for example, an oxygen atom bonded to the terminal group and a -CH2- group and / or a -CH< group bonded to the oxygen atom. 1 In the H-NMR spectrum, the integral value of the peak at 3.2 ppm to 3.8 ppm accounts for a large proportion of the total integral value of this peak, the integral value of the peak of the hydrogen atom of the -CH2- group, and the integral value of the peak of the hydrogen atom of the -CH< group. This proportion is, for example, 50% or more, and may be 80% or more. From the viewpoint of reducing the generation of hydrogen gas and increasing the efficiency of the gas absorption reaction, the above proportion is preferably 85% or more, and more preferably 90% or more. For example, when an ester compound has an -OH group at its terminal and has a -CH2- group and / or a -CH< group bonded to the oxygen atom of the -OH group, 1 In the H-NMR spectrum, the peaks of the hydrogen atoms of the -CH2- group and the -CH< group have chemical shifts in the range of more than 3.8 ppm to 4.0 ppm.

[0089] The negative electrode material may contain one type of ester compound or two or more types of ester compounds.

[0090] The ester compound may include, for example, a compound having an Mn of 50,000 or less, a compound having an Mn of 10,000 or less, a compound having an Mn of 5,000 or less, or a compound having an Mn of 2,000 or less. From the viewpoint of further reducing the amount of hydrogen gas generated, the Mn of such a compound may be 300 or more. As the ester compound, two or more compounds having different Mn may be used. In other words, the ester compound may have multiple Mn peaks in the molecular weight distribution. In this specification, the Mn of the ester compound is a value measured using polyethylene glycol as a standard substance. The Mn of the ester compound is measured by gel permeation chromatography (GPC).

[0091] The content of the ester compound in the negative electrode material is 30 ppm or more by mass. From the viewpoint of further suppressing the loss of the liquid, the content of the ester compound is preferably 50 ppm or more by mass, more preferably 100 ppm or more by mass. The content of the ester compound in the negative electrode material may be 250 ppm or less by mass. From the viewpoint of ensuring a higher PSOC life performance, the content of the ester compound is preferably 220 ppm or less by mass, more preferably 200 ppm or less by mass.

[0092] The content of the ester compound in the negative electrode material may be, on a mass basis, 30 ppm or more (or 50 ppm or more) and 250 ppm or less, 30 ppm or more (or 50 ppm or more) and 220 ppm or less, 30 ppm or more (or 50 ppm or more) and 200 ppm or less, 100 ppm or more and 250 ppm or less (or 220 ppm or less), or 100 ppm or more and 200 ppm or less.

[0093] (Organic shrink-proofing agent) Organic shrink-proofing agents are generally classified into lignin compounds and synthetic organic shrink-proofing agents. Synthetic organic shrink-proofing agents can also be said to be organic shrink-proofing agents other than lignin compounds. Examples of lignin compounds include lignin and lignin derivatives (e.g., lignin sulfonic acid or its salt (e.g., alkali metal salt such as sodium salt)).

[0094] The synthetic organic shrink-proofing agent is an organic compound (e.g., an organic polymer) containing a sulfur element, and generally contains a plurality of aromatic rings in the molecule and a sulfur element as a sulfur-containing group. Among the sulfur-containing groups, a sulfonic acid group or a sulfonyl group, which are stable, is preferred. The sulfonic acid group may be in an acid form or in a salt form such as a Na salt. An organic shrink-proofing agent having at least a sulfonic acid group may be used.

[0095] As the organic shrink-proofing agent, it is also preferable to use a condensation product containing at least an aromatic compound unit. Such a condensation product can be, for example, a condensation product of an aromatic compound with an aldehyde compound (at least one selected from the group consisting of aldehydes (e.g., formaldehyde) and their condensates). The organic shrink-proofing agent may contain one type of aromatic compound unit, or may contain two or more types of aromatic compound units. The aromatic compound unit refers to a unit derived from an aromatic compound incorporated in the condensation product.

[0096] As the aromatic compound, bisarene compounds [bisphenol compounds, hydroxybiphenyl compounds, bisarene compounds having an amino group (bisarylalkane compounds having an amino group, bisarylsulfone compounds having an amino group, biphenyl compounds having an amino group, etc.), hydroxyarene compounds (hydroxynaphthalene compounds, phenol compounds, etc.), aminoarene compounds (aminonaphthalene compounds, aniline compounds (aminobenzenesulfonic acid, alkylaminobenzenesulfonic acid, etc.)), etc.] are preferred. The aromatic compound may further have a substituent. The organic shrinkage inhibitor may contain one or more of the residues of these compounds. As the bisphenol compound, bisphenol A, bisphenol S, bisphenol F, etc. are preferred.

[0097] The condensate may contain at least a unit of an aromatic compound having a sulfur-containing group (such as a bisphenol compound having a sulfur-containing group). The sulfur-containing group may be directly bonded to an aromatic ring contained in the compound, or may be bonded to the aromatic ring as an alkyl chain having a sulfur-containing group. Examples of the sulfur-containing group include a sulfonyl group, a sulfonic acid group, or a salt thereof.

[0098] Also, as the organic shrink-proofing agent, for example, at least one condensate containing at least one selected from the group consisting of the above-mentioned bisarene compound units and monocyclic aromatic compound units (hydroxyarene compounds and / or aminoarene compounds, etc.) may be used. The organic shrink-proofing agent may at least contain a condensate containing a bisarene compound unit and a monocyclic aromatic compound unit (particularly, a hydroxyarene compound). Such a condensate may be a condensate of a bisarene compound and a monocyclic aromatic compound with an aldehyde compound. As the hydroxyarene compound, a phenolsulfonic acid compound (such as phenolsulfonic acid or a substituted product thereof) is preferable. As the aminoarene compound, aminobenzenesulfonic acid, alkylaminobenzenesulfonic acid, etc. are preferable. As the monocyclic aromatic compound, a hydroxyarene compound is preferable.

[0099] However, the organic shrink-proofing agent is not limited to these specific examples. The negative electrode material may contain one type of organic shrink-proofing agent or a combination of two or more types.

[0100] The content of the organic shrink-preventing agent in the negative electrode material is, for example, 0.01% by mass or more. The content of the organic shrink-preventing agent is, for example, 1% by mass or less, and may be 0.5% by mass or less.

[0101] (Barium Sulfate) The content of barium sulfate in the negative electrode material is, for example, 0.05% by mass or more, and may be 0.1% by mass or more. The content of barium sulfate is, for example, 3% by mass or less.

[0102] (others) The unformed negative plate is prepared, for example, by applying or filling a negative electrode paste onto a negative electrode current collector, and then aging and drying. The negative electrode active material in a charged state is sponge-like lead, but the unformed negative plate is usually prepared using lead powder. More specifically, the negative electrode paste used to prepare the unformed negative plate is prepared, for example, by adding water and sulfuric acid (or an aqueous sulfuric acid solution) to lead powder, graphite, an ester compound, and various additives as necessary (organic shrinkage inhibitor, carbonaceous material other than graphite, barium sulfate, etc.), and kneading them. When aging, it is preferable to age the unformed negative plate at a temperature higher than room temperature and at a high humidity. The negative plate is prepared, for example, by chemically forming the unformed negative plate.

[0103] The formation may be carried out, for example, by placing a plate group including unformed negative plates and an electrolyte containing sulfuric acid in a lead-acid battery container, and charging the plate group in a state in which the electrolyte is saturated with the plate group. However, the formation may also be carried out before assembling the lead-acid battery or the plate group. The formation produces spongy lead.

[0104] (Analysis or measurement of negative electrode material) The analysis or measurement of the negative electrode material is carried out on a negative plate taken from a fully charged lead-acid battery.

[0105] Prior to the analysis or measurement, the negative electrode material is extracted from the negative plate by the following procedure.

[0106] First, a fully charged lead-acid battery is disassembled to obtain a negative plate to be analyzed. The obtained negative plate is washed with water to remove sulfuric acid from the negative plate. The washing is performed by pressing a pH test paper against the washed surface of the negative plate until it is confirmed that the color of the test paper does not change. However, the washing time is within 2 hours. The washed negative plate is dried at 60°C ± 5°C for about 6 hours in a reduced pressure environment. If the negative plate contains an adhesive material after drying, the adhesive material is removed by peeling. The mass of the dried material (negative plate) is measured. Next, the negative electrode material is scraped off from the negative electrode collector and separated to obtain a sample (hereinafter referred to as sample B). Sample B is crushed as necessary and used for analysis of the components of the negative electrode material.

[0107] (Analysis of components in negative electrode materials) (a) Quantitative analysis of carbonaceous materials A predetermined amount of the crushed sample B is taken and the mass is measured. 30 mL of nitric acid solution with a concentration of 60% by mass per 5 g of sample B is added to this sample B and heated at 70°C ± 5°C. 10 g of disodium ethylenediaminetetraacetate, 30 mL of ammonia water with a concentration of 28% by mass, and 100 mL of water are added to the resulting mixture with respect to 5 g of sample B, and heating is continued to dissolve the soluble matter. In this way, sample B is pretreated. The dispersion obtained by the pretreatment is filtered using a membrane filter (0.1 μm mesh) to recover the solid matter. The recovered sample is sieved through a 500 μm mesh to remove large-sized components (such as reinforcing materials), and the components that passed through the sieve are recovered as carbonaceous material. The mass of the recovered carbonaceous material is measured.

[0108] When the recovered carbonaceous material is wet sieved using a sieve with 32 μm mesh, the carbonaceous material that does not pass through the sieve and remains on the sieve has a large particle size and is essentially equivalent to graphite. Therefore, the carbonaceous material that remains on the sieve is treated as graphite (first carbonaceous material). Also, the carbonaceous material that passes through the sieve is treated as a carbonaceous material other than graphite (second carbonaceous material). In other words, the particle size of each carbonaceous material is based on the size of the sieve mesh. For wet sieving, JIS Z8815:1994 can be referred to.

[0109] Specifically, the carbonaceous material is placed on a sieve with 32 μm mesh, and sieved by gently shaking the sieve for 5 minutes while spraying ion-exchanged water. The first carbonaceous material remaining on the sieve is collected from the sieve by pouring ion-exchanged water over it, and separated from the ion-exchanged water by filtration. The second carbonaceous material that passed through the sieve is collected by filtration using a nitrocellulose membrane filter (0.1 μm mesh). The collected first and second carbonaceous materials are each dried at a temperature of 100°C ± 5°C for 2 hours. As the sieve with 32 μm mesh, one having a sieve mesh with a nominal mesh size of 32 μm as specified in JIS Z 8801-1:2006 is used.

[0110] The mass of the recovered first carbonaceous material is measured. The ratio (mass%) of this mass to the measured mass of sample A is calculated to be the content (mass%) of the first carbonaceous material in the negative electrode material. The proportion of the first carbonaceous material in the total of the first carbonaceous material and the second carbonaceous material is calculated by calculating the ratio (mass%) of the measured mass of the first carbonaceous material to the mass of the carbonaceous materials recovered above.

[0111] (b) Qualitative analysis of ester compounds (b-1) OxyC 2-4 Analysis of alkylene units A crushed sample B is used. 150.0±0.1 mL of chloroform is added to 100.0±0.1 g of sample B, and the mixture is stirred at 20±5° C. for 16 hours to extract the ester compound. The solid content is then removed by filtration. The ester compound is identified by obtaining information from at least one of infrared spectroscopy, ultraviolet-visible absorption spectroscopy, NMR spectroscopy, LC-MS, and pyrolysis GC-MS for the chloroform solution in which the ester compound obtained by extraction is dissolved, or the ester compound obtained by drying the chloroform solution.

[0112] The chloroform soluble matter is recovered by distilling off the chloroform under reduced pressure from the chloroform solution in which the ester compound obtained by extraction is dissolved. The chloroform soluble matter is dissolved in deuterated chloroform and then subjected to the following conditions: 1 1H-NMR spectrum is measured. 1 From the H-NMR spectrum, a peak with a chemical shift in the range of 3.2 ppm to 3.8 ppm is confirmed. Also, from the peak in this range, oxy C 2-4 Identify the type of alkylene unit.

[0113] Equipment: AL400 nuclear magnetic resonance equipment manufactured by JEOL Ltd. Observation frequency: 395.88MHz Pulse width: 6.30μs Pulse repetition time: 74.1411 seconds Accumulation count: 32 Measurement temperature: room temperature (20~35℃) Standard: 7.24 ppm Sample tube diameter: 5mm 1 From the H-NMR spectrum, the integral value (V1) of the peaks present in the chemical shift range of 3.2 ppm to 3.8 ppm is calculated. In addition, for each of the hydrogen atoms of the -CH2- group and -CH< group bonded to the oxygen atom bonded to the terminal group of the ester compound, 1The sum (V2) of the integral values ​​of the peaks in the H-NMR spectrum is calculated. Then, from V1 and V2, the percentage of V1 in the sum of V1 and V2 (=V1 / (V1+V2)×100(%)) is calculated.

[0114] In addition, in the qualitative analysis, 1 When calculating the integral value of a peak in a H-NMR spectrum, 1 In the H-NMR spectrum, two points without significant signals are determined so as to sandwich the corresponding peak, and each integral value is calculated using a straight line connecting these two points as a baseline. For example, for a peak that exists in a chemical shift range of 3.2 ppm to 3.8 ppm, a straight line connecting two points on the spectrum between 3.2 ppm and 3.8 ppm is used as the baseline. For example, for a peak that exists in a chemical shift range of more than 3.8 ppm to 4.0 ppm, a straight line connecting two points on the spectrum between 3.8 ppm and 4.0 ppm is used as the baseline.

[0115] (b-2) Analysis of hydrophobic groups in esterified products In the above (b-1), a predetermined amount of the ester compound obtained by drying the chloroform solution in which the ester compound obtained by extraction is dissolved is collected, and an aqueous potassium hydroxide solution is added. This causes the ester compound to be saponified, producing a fatty acid potassium salt and a hydroxy compound. The above aqueous water-soluble potassium solution is added until the saponification is complete. The fatty acid potassium salt is converted into a fatty acid methyl ester by adding and mixing a solution of methanol and boron trifluoride to the resulting mixture. The resulting mixture is analyzed by pyrolysis GC-MS under the following conditions to identify the hydrophobic group contained in the ester compound. Analytical equipment: Shimadzu Corporation, high-performance general-purpose gas chromatogram GC-2014 Column: DEGS (diethylene glycol succinate) 2.1m Oven temperature: 180~120℃ Inlet temperature: 240℃ Detector temperature: 240℃ Carrier gas: He (flow rate: 50 mL / min) Injection volume: 1μL~2μL

[0116] (b-3) Quantitative analysis of ester compounds The appropriate amount of the chloroform soluble matter was measured with an accuracy of ±0.0001 g. r (g) Dissolve in deuterated chloroform together with tetrachloroethane (TCE), 1 Measure the H-NMR spectrum. The integral value (S a ) and the integral value of the peak due to TCE (S r ) and calculate the mass-based content C of the ester compound in the negative electrode material from the following formula: n Calculate the ppm.

[0117] C n =S a / S r ×N r / N a ×M a / M r ×m r / m×1000000 (In the formula, M a The molecular weight of the structure that shows a peak in the chemical shift range of 3.2 to 3.8 ppm (more specifically, oxy C 2-4 (the molecular weight of the repeating structure of alkylene units) and N a is the number of hydrogen atoms attached to the carbon atoms in the main chain of the repeating unit. r、 M r are the number of hydrogen atoms contained in the molecule of the reference material, the molecular weight of the reference material, and m (g) is the mass of the negative electrode material used for extraction.) In addition, the standard substance in this analysis is TCE, so N r =2, M r = 168. Also, m = 100.

[0118] For example, when the ester compound is an ester of polypropylene glycol, M a is 58, and N ais 3. When the ester compound is an ester of polyethylene glycol, M a is 44, and N a is 4. In the case of copolymers, N a and M. a are the N of each monomer unit, a Value and M a The value is calculated by averaging the molar ratio (mol %) of each monomer unit contained in the repeating structure.

[0119] In addition, in the quantitative analysis, 1 The integral value of the peak in the H-NMR spectrum is determined using data processing software “ALICE” manufactured by JEOL Ltd.

[0120] (b-4) Mn measurement of ester compounds Using the above chloroform solubles, GPC measurement of the ester compounds is carried out using the following apparatus under the following conditions. Separately, a calibration curve (calibration curve) is created from a plot of Mn of the standard substance versus elution time. Based on this calibration curve and the GPC measurement results of the ester compounds, the Mn of the ester compounds is calculated. However, the esterified products may be in a decomposed state in the chloroform solubles.

[0121] Analysis system: 20A system (Shimadzu Corporation) Column: Two GPC KF-805L (Shodex) columns connected in series Column temperature: 30℃±1℃ Mobile phase: Tetrahydrofuran Flow rate: 1mL / min. Concentration: 0.20% by mass Injection volume: 10μL Standard substance: polyethylene glycol (Mn=2,000,000, 200,000, 20,000, 2,000, 200) Detector: Differential refractive index detector (Shodex RI-201H)

[0122] (c) Quantitative determination of organic shrinkage inhibitor A predetermined amount of the crushed sample B is collected, weighed, and immersed in a 1 mol / L NaOH aqueous solution to extract the organic shrink-preventing agent. Insoluble components are removed by filtration from the NaOH aqueous solution containing the extracted organic shrink-preventing agent, and the filtrate (hereinafter also referred to as filtrate C) is collected.

[0123] A predetermined amount of filtrate C is measured, desalted, concentrated, and dried to obtain a powder of the organic shrink-preventing agent (hereinafter also referred to as sample D). Desalting is performed using a desalting column, by passing filtrate C through an ion exchange membrane, or by placing filtrate C in a dialysis tube and immersing it in distilled water.

[0124] The organic shrinkage inhibitor is identified by combining information obtained from the infrared spectrum of sample D, the ultraviolet-visible absorption spectrum of a solution obtained by dissolving sample D in distilled water or the like, the nuclear magnetic resonance (NMR) spectrum of a solution obtained by dissolving sample D in a solvent such as heavy water, or information obtained from pyrolysis GC-MS, which can obtain information on the individual compounds that make up the substance.

[0125] The ultraviolet-visible absorption spectrum of the filtrate C is measured. The content of the organic shrink inhibitor in the negative electrode material is quantified from the spectral intensity, the calibration curve prepared in advance, the measured amount of filtrate C, and the mass of sample B provided for analysis. If the structural formula of the organic shrink inhibitor to be analyzed cannot be precisely identified and a calibration curve of the same organic shrink inhibitor cannot be used, a calibration curve is prepared using an available organic shrink inhibitor that exhibits a similar ultraviolet-visible absorption spectrum, infrared spectroscopy spectrum, NMR spectrum, etc. to the organic shrink inhibitor to be analyzed.

[0126] (d) Determination of barium sulfate 50 ml of 20% by mass nitric acid is added to 10 g of the crushed sample B, and the mixture is heated for about 20 minutes to dissolve the lead components as lead nitrate. Next, the solution containing lead nitrate is filtered to separate the solids such as carbonaceous materials and barium sulfate.

[0127] The obtained solid content is dispersed in water to obtain a dispersion, and then a sieve is used to remove components other than the carbonaceous material and barium sulfate (e.g., reinforcing material) from the dispersion. Next, the dispersion is subjected to suction filtration using a membrane filter whose mass has been measured in advance, and the membrane filter together with the filtered sample is dried in a dryer at 110°C ± 5°C. The obtained sample is a mixed sample of the carbonaceous material and barium sulfate (hereinafter referred to as sample E). The mass of sample E is measured by subtracting the mass of the membrane filter from the total mass of sample E and the membrane filter after drying. Then, sample E after drying is placed in a crucible together with the membrane filter and incinerated at 1300°C or higher. The remaining residue is barium oxide. The mass of barium oxide is converted to the mass of barium sulfate to determine the mass of barium sulfate.

[0128] (Separator) A separator may be disposed between the negative electrode plate and the positive electrode plate, and may be made of at least one material selected from a nonwoven fabric and a microporous membrane.

[0129] A nonwoven fabric is a mat in which fibers are intertwined without being woven, and is mainly composed of fibers. For example, 60% or more by mass of the nonwoven fabric is made of fibers. As the fibers, glass fibers, polymer fibers (polyolefin fibers, acrylic fibers, polyester fibers (polyethylene terephthalate fibers, etc.), pulp fibers, etc. can be used. Among them, glass fibers are preferable. The nonwoven fabric may contain components other than fibers (for example, acid-resistant inorganic powder, polymers as binders), etc.

[0130] The microporous membrane is a porous sheet mainly composed of components other than fiber components, and can be obtained, for example, by extruding a composition containing a pore-forming agent into a sheet, and then removing the pore-forming agent to form pores. The microporous membrane is preferably made of an acid-resistant material, and is preferably a microporous membrane mainly composed of a polymer component. The polymer component is preferably polyolefin (polyethylene, polypropylene, etc.). The pore-forming agent can be at least one selected from the group consisting of polymer powder and oil.

[0131] The separator may be, for example, composed of only a nonwoven fabric or only a microporous membrane. Furthermore, the separator may be, as necessary, a laminate of a nonwoven fabric and a microporous membrane, a laminate of different or the same materials, or a laminate of different or the same materials with recesses and projections interlocked.

[0132] The separator may be in a sheet shape or may be formed in a bag shape. A sheet-shaped separator may be sandwiched between the positive electrode plate and the negative electrode plate. Also, the electrode plate may be sandwiched between a folded sheet-shaped separator. In this case, the positive electrode plate sandwiched between the folded sheet-shaped separator and the negative electrode plate sandwiched between the folded sheet-shaped separator may be stacked, or one of the positive electrode plate and the negative electrode plate may be sandwiched between the folded sheet-shaped separator and stacked with the other electrode plate. Also, the sheet-shaped separator may be folded into a bellows shape, and the positive electrode plate and the negative electrode plate may be sandwiched between the bellows-shaped separator so that the separator is interposed between them. When a separator folded like an accordion is used, the separator may be arranged so that the folded portion is along the horizontal direction of the lead-acid battery (for example, so that the folded portion is parallel to the horizontal direction) or along the vertical direction (for example, so that the folded portion is parallel to the vertical direction). In a separator folded like an accordion, recesses are formed alternately on both main surfaces of the separator. Since the upper portions of the positive and negative plates usually have lugs, when the separator is arranged so that the folded portion is along the horizontal direction of the lead-acid battery, the positive and negative plates are arranged only in the recesses on one main surface side of the separator (that is, a double separator is interposed between the adjacent positive and negative plates). When the separator is arranged so that the folded portion is aligned with the vertical direction of the lead-acid battery, the positive electrode plate can be accommodated in the recess on one main surface side, and the negative electrode plate can be accommodated in the recess on the other main surface side (that is, a single layer of separator can be interposed between adjacent positive and negative electrode plates.) When a pouch-shaped separator is used, the pouch-shaped separator may accommodate either the positive or negative electrode plate.

[0133] The separator may have at least a rib (first rib) protruding toward the positive electrode plate. When the separator has the first rib, the space between the first rib surrounded by the separator (more specifically, the base portion) and the positive electrode plate becomes narrower and more closed. Due to the presence of the first rib, the oxygen concentration in the space surrounded by the separator and the positive electrode plate increases, so that a large amount of oxygen is easily supplied to the negative electrode plate. Therefore, the gas absorption reaction occurs more easily, and the amount of liquid loss can be further reduced. The separator may have a rib (second rib) protruding toward the negative electrode plate as necessary. The first rib is formed, for example, in a portion of the separator facing the portion where the positive electrode material is present. The second rib is formed, for example, in a portion of the separator facing the portion where the negative electrode material is present. The separator usually has a base portion. In a separator having a rib, the rib protrudes from the surface of the base portion. The base portion of the separator refers to the portion of the separator that does not include protrusions such as ribs, and is a sheet-like portion that defines the outer shape of the separator.

[0134] The average height of the first rib may be 0.3 mm or more. From the viewpoint of ensuring a high capacity, the average height of the first rib may be 1.0 mm or less, or may be 0.7 mm or less.

[0135] The separator may have a plurality of first ribs. The plurality of first ribs may extend, for example, along the longitudinal direction of the separator. In this specification, the longitudinal direction of the separator refers to the direction along the vertical direction (in other words, the height direction of the electrode plates) in the flooded lead-acid battery housing the separator. The acute angle between the average direction in which the first ribs extend and the height direction of the electrode plates (or the vertical direction in the flooded lead-acid battery) is, for example, 30° or less, and may be 15° or less. The average direction in which the first ribs extend and the height direction of the electrode plates (or the vertical direction in the lead-acid battery) may be parallel.

[0136] The average spacing between the first ribs may be 1.3 cm or less. From the viewpoint of facilitating the formation of a more closed space between the base portion and the positive electrode plate between adjacent first ribs, the average spacing between the first ribs may be 1.0 cm or less. The average spacing between the first ribs refers to the average spacing between adjacent first ribs. The average spacing between the first ribs may be 4 mm or more.

[0137] The average spacing of the first ribs is measured using a separator sample A for measurement. More specifically, the spacing between adjacent first ribs is measured with a vernier caliper at multiple locations on the separator included in the electrode plate group, and then averaged. If the battery includes multiple electrode plate groups, the average spacing of the first ribs is determined for one of the outermost electrode plate groups and one of the electrode plate groups near the center, and then averaged.

[0138] The average height of the second rib may be 0.10 mm or less. The average height of the second rib may be 0.02 mm or more. From the viewpoint of efficiently carrying out the gas absorption reaction on the negative electrode plate side, it is preferable that the average height of the second rib is low, for example, 0.05 mm or less. The separator may not have the second rib.

[0139] The separator may have a plurality of second ribs. The plurality of second ribs may extend along the longitudinal direction of the separator in the same manner as the first rib. The average spacing of the plurality of second ribs may be selected from the ranges described for the first rib.

[0140] The separator may have a rib (third rib) other than the first rib on the main surface (first main surface) on which the first rib is formed. The third rib is a rib formed in an area of ​​the first main surface that does not face the positive electrode material. The separator may also have a rib (fourth rib) formed in an area of ​​the main surface (second main surface) opposite to the main surface on which the first rib is formed, that does not face the negative electrode material, as necessary. When the separator has a second rib, the second rib is formed in an area of ​​the second main surface that faces the negative electrode material.

[0141] The average thickness of the base portion may be 0.10 mm or more, or may be 0.15 mm or more. The average thickness of the base portion may be 0.30 mm or less.

[0142] (electrolyte) The electrolyte is an aqueous solution containing sulfuric acid. The electrolyte may contain a polymer that swells in the electrolyte, if necessary. The electrolyte is preferably fluid at the temperature at which it is used, and more preferably liquid at 25°C.

[0143] The electrolytic solution may contain cations (e.g., metal cations) and / or anions (e.g., anions other than sulfate anions (e.g., phosphate ions)) as necessary. Examples of metal cations include at least one selected from the group consisting of Na ions, Li ions, Mg ions, and Al ions.

[0144] From the viewpoint of further suppressing the permeation short circuit, the concentration of the metal cation in the electrolyte may be 0.03 mol / L or more. From the viewpoint of ensuring high charge acceptance in regenerative charging, the concentration of the metal cation in the electrolyte may be 0.5 mol / L or less, 0.3 mol / L or less, or 0.1 mol / L or less.

[0145] The density of the electrolyte in a fully charged lead-acid battery at 20°C is, for example, 1.20 g cm -3 The density of the electrolyte at 20°C is 1.35 g cm -3 Here, the density of the electrolytic solution is the density of the electrolytic solution (more specifically, an aqueous sulfuric acid solution) in a state that does not contain additives such as metal cations that are added to the electrolytic solution.

[0146] (others) A lead-acid battery may include one cell or may include two or more cells. When a lead-acid battery includes multiple cells (in other words, multiple plate groups), the multiple plate groups may be connected in series.

[0147] The ratio Ra (=(S1-Sg) / Sg=Se / Sg) may be 0.30 or less. From the viewpoint of further suppressing the loss of electrolyte, the ratio Ra may be 0.25 or less, or 0.24 or less, or may be 0.20 or less. From the viewpoint of ensuring higher PSOC life performance, the ratio Ra is preferably 0.20 or less. The wall surface (side wall or partition wall) of the cell chamber is close to the periphery of the electrode plate group, and the volume in which the electrolyte can be retained is limited. When the ratio Ra is 0.20 or less, the electrolyte present outside the electrode plate group is relatively small, and the upward convection of the electrolyte between the electrode plate group and the battery case wall that occurs during charging is easily blocked. Therefore, it is considered that stratification is suppressed and deterioration of the electrode plate is suppressed, thereby obtaining high PSOC life performance.

[0148] The ratio Ra is determined at a portion parallel to the bottom of the cell chamber (or battery case) of a fully charged lead-acid battery, and 4.5 cm to 5.5 cm above the bottom of the cell chamber (more specifically, the inner bottom surface). Based on this determination method, in this specification, the cross section parallel to the bottom of the cell chamber where the ratio Ra is determined is treated as the cross section of a flooded lead-acid battery at a position parallel to the bottom of the cell chamber of a fully charged lead-acid battery, and 5 cm above the bottom of the cell chamber (more specifically, the inner bottom surface).

[0149] More specifically, the ratio Ra can be found by the following procedure. First, the cross-sectional area S1 inside the cell chamber (or battery case) is found by the following procedure. After removing the electrode plate group and electrolyte from the battery case, the battery case is washed with water, dried, and then placed on a flat surface. Water is then poured in parallel to the bottom of the battery case up to a height of 4.5 cm from the bottom. Next, water is poured in up to a height of 5.5 cm from the bottom, and the volume of the water poured in (cm 3 ) is calculated by dividing the volume of the added water by the height of 1 cm. 2 If the battery case is divided into multiple cells, the cross-sectional area (cm2) of the inside of all the cells is calculated in the same manner as for the battery case. 2 ) by the number of cell chambers to obtain the cross-sectional area S1 (cm 2In addition, in a lead-acid battery, if there are parts other than the plate group and the electrolyte inside the battery case or cell chamber (for example, other members such as spacers and hollow parts (spaces not filled with electrolyte, etc.)), the cross-sectional area S1 inside the battery case or cell chamber is found using the above procedure with these parts present.

[0150] The plate group taken out of the fully charged lead-acid battery is disassembled into the positive plate, the negative plate, and the separator, and the thickness of the positive plate, the thickness of the negative plate, and the total thickness of the separator are obtained by the above-mentioned procedure. However, at this time, the thickness of each plate is measured with a vernier caliper at a position corresponding to a height of 5 cm from the bottom (more specifically, the inner bottom surface) of the cell chamber (or battery case). The thickness of the positive plate × the number of positive plates, the thickness of the negative plate × the number of negative plates, and the total thickness of the separator × the number between the positive plate and the negative plate (in the case of a bag-shaped separator, the total thickness of the separator × the number of bag-shaped separators × 2) are measured and added together. This determines the thickness (dimension y) of the plate group in the stacking direction (y direction). Next, the width (dimension in the x direction) of the plate at a height of 5 cm from the bottom (more specifically, the inner bottom surface) of the cell chamber (or battery case) is measured with a scale. When the widths of the positive and negative plates are different, the average width is calculated and used as the plate width (dimension in the x direction of the plate group). The cross-sectional area Sg of the plate group is calculated by multiplying this plate width by the thickness (dimension y) of the plate group in the stacking direction. The total thickness of the separator corresponds to the sum of the separator thicknesses t mentioned above.

[0151] From S1 and Sg, Se=S1-Sg is calculated. Then, the ratio Ra is calculated by dividing Se by Sg. In a lead-acid battery containing multiple cells, the ratio Ra is calculated by averaging the ratios Ra calculated for the cells located at the ends and the cells located near the center.

[0152] When calculating the ratio Ra, the following points should be noted: First, even when pressure is applied to the plate assembly in the thickness direction, a gap may exist between the plate assembly and the battery case (or cell chamber). For example, if the outermost member is a separator with ribs on its outer surface, and the ribs face the side wall or partition wall of the battery case, the height of the separator ribs is not included in the y-direction dimension of the plate assembly. On the other hand, if the tip of the rib is in contact with the side wall or partition wall, the height of the rib controls the y-direction dimension of the cross-sectional area Sg of the plate assembly. Since the separator ribs have a certain degree of flexibility, they may be deformed by being pressed by the side wall or partition wall. In that case, the height of the rib after deformation controls the y-direction dimension of the cross-sectional area Sg of the plate assembly.

[0153] Similarly, when determining the dimension in the y direction of the cross-sectional area Sg of the electrode plate pack, if the side wall or partition of the battery case has ribs, the height of the ribs is not included in the dimension in the y direction. If both the side wall or partition and the separator have ribs and the tips of the ribs are in contact with the side wall or partition, the sum of the height of the separator rib (the height of the rib after deformation if it is deformed) and the height of the rib of the side wall or partition determines the dimension in the y direction of the cross-sectional area Sg of the electrode plate pack.

[0154] In a lead-acid battery, the opening of the battery case is usually closed with a lid. The lid includes, for example, a negative electrode terminal and a positive electrode terminal. The lid may have a single structure (single lid) or a double structure including an inner lid and an outer lid (or a top lid). A lid having a double structure may include a reflux structure between the inner lid and the outer lid for returning the electrolyte to the inside of the battery (inside the inner lid) from a reflux port provided in the inner lid.

[0155] The lead-acid battery can be obtained, for example, by a manufacturing method including a step of housing a plate group and an electrolyte in a cell chamber of a battery case. Each cell of the lead-acid battery includes a plate group and an electrolyte housed in each cell chamber. The plate group is assembled, for example, by stacking a positive electrode plate, a negative electrode plate, and a separator such that the separator is interposed between the positive electrode plate and the negative electrode plate prior to housing in the cell chamber. Each of the positive electrode plate, the negative electrode plate, and the separator is usually prepared prior to assembly of the plate group. The electrolyte is prepared prior to housing in the cell chamber. When the lead-acid battery has one plate group, the battery case does not need to be divided into a plurality of cell chambers, and the plate group and the electrolyte may be housed in the battery case.

[0156] The method for producing a lead-acid battery may include, after the step of housing the electrode plate group and the electrolyte in the cell chamber, a step of forming at least one of the positive electrode plate and the negative electrode plate, as necessary.

[0157] An external appearance and an internal structure of an example of a flooded lead-acid battery according to one aspect of the present invention are shown in Fig. 1. However, the lead-acid battery according to one aspect of the present disclosure is not limited to the following embodiment.

[0158] The flooded lead-acid battery 1 includes a battery case 12 that contains a plate group 11 and an electrolyte (not shown). The inside of the battery case 12 is divided into a plurality of cell chambers 14 by partition walls 13. Each cell chamber 14 contains one of the plate groups 11. The opening of the battery case 12 is closed by a lid 15 that includes a positive electrode terminal 16 and a negative electrode terminal 17. The lid 15 is provided with a vent plug 18 for each cell chamber. When refilling with water, the vent plug 18 is removed and refilling liquid is added. The vent plug 18 may have a function of discharging gas generated in the cell chamber 14 to the outside of the battery.

[0159] The electrode plate group 11 is formed by alternately stacking a plurality of negative electrode plates 3 and positive electrode plates 2 with separators 4 interposed therebetween. Here, the separator 4 is bag-shaped and packs the positive electrode plates 2 one by one. However, the form of the separator is not particularly limited. In the cell chamber 14 located at one end of the battery case 12, the positive electrode shelf 6 that connects the ears 2a of the plurality of positive electrode plates 2 in parallel is connected to the through connector 8, and the negative electrode shelf 5 that connects the ears 3a of the plurality of negative electrode plates 3 in parallel is connected to the negative electrode column 7. The negative electrode column 7 is connected to a negative electrode terminal 17 outside the lid 15. In the cell chamber 14 located at the other end of the battery case 12, the positive electrode column 9 is connected to the positive electrode shelf 6, and the through connector 8 is connected to the negative electrode shelf 5. The positive electrode column 9 is connected to a positive electrode terminal 16 outside the lid 15. Each of the through-connectors 8 passes through a through hole provided in the partition wall 13 and connects the electrode plate groups 11 of adjacent cell chambers 14 in series.

[0160] The positive electrode shelf 6 is formed by welding, for example, by a cast-on-strap method or a burning method, the ears 2a provided on the upper part of each positive electrode plate 2. The negative electrode shelf 5 is also formed by welding, in the same manner as the positive electrode shelf 6, the ears 3a provided on the upper part of each negative electrode plate 3.

[0161] Although the lid 15 of the lead-acid battery has a single structure (single lid), this is not limited to the illustrated example. For example, the lid 15 may have a double structure as described above. The lid having a double structure may have a reflux structure.

[0162] [Example] The present invention will be specifically described below based on examples and comparative examples, but the present invention is not limited to the following examples.

[0163] Flooded lead-acid batteries E1 to E21 and C1 to C15 (1) Preparation of lead-acid batteries (a) Preparation of the negative electrode plate Lead powder, water, dilute sulfuric acid, sodium lignin sulfonate as an organic shrinkage inhibitor, barium sulfate, carbon black, graphite, and an ester compound (or polypropylene glycol: PPG) are mixed to obtain a negative electrode paste. At this time, the contents of the organic shrinkage inhibitor, barium sulfate, and carbon black in the negative electrode material obtained by the above-mentioned procedures are 0.2 mass%, 0.6 mass%, and 0.3 mass%, respectively, and the contents of the graphite and ester compound (or PPG) in the negative electrode material are adjusted to the values ​​shown in the table. The negative electrode paste is filled into the mesh part of an expanded lattice made of Pb-Ca-Sn alloy and aged and dried. In this way, an unformed negative electrode plate is obtained.

[0164] The ester compounds or PPGs in the table are as follows. 1 In the H-NMR spectrum, the percentage of the integral of the peak between 3.2 ppm and 3.8 ppm to the total integral of this peak, the integral of the peak of the hydrogen atom of the -CH2- group bonded to the oxygen atom, and the integral of the peak of the hydrogen atom of the -CH< group bonded to the oxygen atom is 96 to 100%. (i) PEG oleate: polyethylene glycol oleate (Mn: 500) (ii) PEG dilaurate: polyethylene glycol dilaurate (Mn: 630) (iii) PEG dioleate: polyethylene glycol dioleate (Mn: 880) (iv) PEG distearate: polyethylene glycol distearate (Mn: 490) (v) PPG (Mn:2000)

[0165] (b) Preparation of the positive electrode plate Lead powder, water, and dilute sulfuric acid are mixed to obtain a positive electrode paste. The positive electrode paste is filled into the mesh of an expanded grid made of a Pb-Ca-Sn alloy as a positive electrode current collector, and then aged and dried. In this manner, an unformed positive electrode plate is obtained. When obtaining the positive electrode paste, antimony trioxide is added as necessary. The amount of antimony trioxide added is adjusted so that the content of Sb element in the positive electrode plate is the value shown in the table.

[0166] (c) Fabrication of flooded lead-acid battery The battery has a nominal voltage of 12V (6 cells) and a rated 20-hour rate capacity of 59Ah. The battery plate group is composed of seven positive plates and eight negative plates. First, the unformed positive plates are placed in a pouch-shaped separator and stacked alternately with the negative plates. The resulting plate group composed of unformed plates is placed in a battery container together with an electrolyte (aqueous sulfuric acid solution), and formation is carried out in the container to produce a flooded lead-acid battery. In Table 4, the specific Ra obtained by the above-mentioned procedure is adjusted using a spacer to the value shown in Table 4. The density of the electrolyte in a fully charged lead-acid battery at 20°C is 1.285 g cm without additives such as metal cations. -3 The above chemical conversion brings the lead-acid battery into a fully charged state.

[0167] (2) Evaluation The following evaluations are performed using batteries with a nominal voltage of 12 V (6 cells) produced in the Examples or Comparative Examples. When the following evaluations are performed using other batteries, the evaluations are performed at a voltage that matches the number of cells in the battery.

[0168] (a) Amount of liquid reduction Measure the mass of the battery (M0). Place the battery in a water bath at 60°C ± 2°C and charge it at a constant voltage of 14.4 V with a maximum current of 50 A for 42 days. When the liquid level reaches the minimum liquid level line during charging, add water up to the maximum liquid level line and record the amount of water added. After charging, remove the battery from the water bath and leave it to reach room temperature (20-35°C), then measure the mass of the battery (M1). Subtract M1 from M0 to obtain the total amount of water added (M a) is added together to determine the amount of loss of battery liquid. In Tables 1 to 3, the amount of loss of battery liquid in battery C05 is set to 100, and in Table 4, the amount of loss of battery liquid in battery E03 is set to 100, and the amount of loss of battery liquid in each battery is evaluated as a relative value. The smaller this relative value, the more suppressed the loss of battery liquid is.

[0169] (b) PSOC life performance The PSOC life performance of flooded lead-acid batteries is evaluated by the following procedure. All steps are carried out in a water bath at 25°C ± 1°C. Steps 1 to 7 are repeated. The charge in step 2 and the discharge in step 3 are counted as one cycle, and the number of cycles when the end-of-discharge voltage in step 3 falls below 10 V is determined. The PSOC life performance of each battery is evaluated in Tables 1 to 3 as a relative value when the number of cycles of battery C05 is taken as 100, and in Table 4 as a relative value when the number of cycles of battery E03 is taken as 100. A larger value indicates better PSOC life performance. Step 1 (conditioning discharge): Discharge for 2.5 hours at a current of 4 x I20A. Step 2 (charging): Set the upper limit current to 7 x I20A and charge at a constant voltage of 14.4V for 40 minutes. Step 3 (discharge): Discharge at a current of 7 x I20A for 30 minutes. Step 4: Repeat steps 2 and 3 for 85 cycles. Step 5 (charging): Set the upper limit current to 2 x I20A and charge at a constant voltage of 16.0V for 18 hours. Step 6 (Discharge): Discharge at a current of I20A until the voltage reaches 10.5V. Step 7 (charging): Set the upper limit current to 5 x I20A and charge at a constant voltage of 16.0V for 24 hours.

[0170] The evaluation results are shown in Tables 1 to 4. In these tables, E1 to E21 are examples, and C1 to C15 are comparative examples.

[0171] [Table 1]

[0172] As shown in Table 1, when (st)>0.10mm, the effect of Sb element increasing the amount of liquid loss is +19 when comparing batteries C08 and C09. The effect of ester compound increasing the amount of liquid loss is -10 when comparing batteries C09 and C10. The effect of graphite increasing the amount of liquid loss is +5 when comparing batteries C08 and C11. From these results, it is expected that the amount of liquid loss when a positive electrode plate containing Sb element is combined with a negative electrode plate containing graphite and an ester compound will be 91+19-10+5=105. In reality, the amount of liquid loss is greater than this value, being 114 (battery C13).

[0173] Even when (st)≦0.10 mm, the effect of Sb element, ester compound, and graphite on increasing the amount of liquid loss shows a similar tendency to the case when (st)>0.10 mm. More specifically, the effect of Sb element on increasing the amount of liquid loss is +18 (comparison between C01 and C03). The effect of ester compound on increasing the amount of liquid loss is -9 (comparison between C03 and C05). The effect of graphite on increasing the amount of liquid loss is +4 (comparison between C01 and C06). From these results, it is expected that the amount of liquid loss when a positive electrode plate containing Sb element is combined with a negative electrode plate containing graphite and ester compound will be 91+18-9+4=104. However, in reality, the amount of liquid loss is 95 (E01), which is significantly reduced from the expected value. The tendency of the amount of liquid loss in battery E01 is completely different from the tendency when (st)>0.10 mm. Moreover, the battery E01 has a higher PSOC life performance than the comparative example. When (st)≦0.10 mm, as (st) becomes smaller, the amount of liquid loss is reduced and the PSOC life performance is improved (E01 to E04). In addition, the same effect can be obtained even when the type of ester compound is changed (E05 to E07). However, when PPG is used instead of the ester compound, the effect of reducing the amount of liquid loss is low and not a very high PSOC life performance can be obtained (C14).

[0174] [Table 2]

[0175] As shown in Table 2, in order to obtain the effect of reducing the amount of liquid loss, the negative electrode material needs to contain a certain amount of ester compound. If the content of the ester compound in the negative electrode material is 30 ppm by mass or more, the effect of reducing the amount of liquid loss can be obtained. From the viewpoint of further suppressing the liquid loss, the content of the ester compound is preferably 50 ppm by mass or more. From the viewpoint of ensuring higher PSOC life performance, the content of the ester compound is preferably 220 ppm by mass or less, and more preferably 200 ppm by mass or less.

[0176] [Table 3]

[0177] As shown in Table 3, from the viewpoint of further reducing the amount of loss of the electrolyte, the content of the Sb element in the positive electrode plate is preferably 0.20 mass% or less, and may be 0.15 mass% or less or 0.10 mass% or less. From the viewpoint of ensuring higher PSOC life performance, the content of the Sb element in the positive electrode plate is preferably 0.01 mass% or more, and more preferably 0.03 mass% or more or 0.05 mass% or more.

[0178] From the viewpoint of further reducing the amount of loss of the electrolyte, the graphite content in the negative electrode material is preferably 2.5% by mass or less, more preferably 2.0% by mass or less or 1.5% by mass or less. From the viewpoint of ensuring a higher PSOC life performance, the graphite content in the negative electrode material is preferably 0.3% by mass or more, more preferably 0.5% by mass or more.

[0179] [Table 4]

[0180] As shown in Table 4, when Ra≦0.20, the amount of liquid loss is further reduced compared to when Ra>0.20. Also, when Ra≦0.20, the PSOC life performance is significantly improved compared to when Ra>0.20. [Industrial Applicability]

[0181] The flooded lead-acid battery according to one aspect of the present invention is suitable for use as an IS lead-acid battery in a vehicle equipped with an idle reduction system. The lead-acid battery can also be suitably used as a starting power source for a vehicle (such as an automobile or motorcycle) or an industrial power storage device (such as a power source for an electric vehicle (such as a forklift)). Note that these are merely examples, and the uses of the flooded lead-acid battery are not limited to these. [Explanation of symbols]

[0182] 1: Liquid lead acid battery 2: Positive electrode plate 2a: Positive electrode plate lug 3: Negative plate 3a: Negative electrode plate lug 4: Separator 5: Negative electrode shelf 6: Positive electrode shelf 7: Negative pole 8: Through connector 9: Positive pole 11: Plate group 12:Battery container 13: Bulkhead 14: Cell Room 15: Lid 16: Positive terminal 17: Negative terminal 18: Liquid outlet plug

Claims

1. A flooded lead-acid battery, The flooded lead-acid battery includes a plate group, an electrolyte, and a cell chamber that accommodates the plate group and the electrolyte, the electrode plate group includes a positive electrode plate, a negative electrode plate, and a separator interposed between the positive electrode plate and the negative electrode plate, The difference between the total distance s between the positive electrode plates and the negative electrode plates facing each other in the electrode plate group and the total thickness t of the separator: (s−t) is 0.10 mm or less; The positive electrode plate contains Sb element, The negative electrode plate includes a negative electrode material, The negative electrode material contains graphite and an ester compound having a repeating structure of oxyalkylene units, A flooded lead-acid battery, wherein the content of the ester compound in the negative electrode material is 30 ppm or more by mass.

2. 2. The flooded lead-acid battery according to claim 1, wherein the content of the ester compound in the negative electrode material is 220 ppm or less by mass.

3. 3. The flooded lead-acid battery according to claim 1, wherein the repeating structure of the oxyalkylene unit includes a repeating structure of an oxyethylene unit.

4. 3. The flooded lead-acid battery according to claim 1, wherein the graphite content in the negative electrode material is 0.3 mass % or more and 2.5 mass % or less.

5. 3. The flooded lead-acid battery according to claim 1, wherein the content of Sb in the positive electrode plate is 0.01% by mass or more and 0.20% by mass or less.

6. 3. The flooded lead-acid battery according to claim 1, wherein in a cross section of the flooded lead-acid battery parallel to a bottom of the cell chamber, a ratio Ra (=Se / Sg) of an area Se (=S1-Sg) obtained by subtracting a cross-sectional area Sg of the plate pack from a cross-sectional area S1 inside the cell chamber to the cross-sectional area Sg of the plate pack is 0.20 or less.

Citation Information

Patent Citations

  • Positive electrode collector for lead storage battery and lead storage battery

    JP2021170429A

  • Lead storage battery

    WO2020241547A1

  • Lead acid storage battery

    WO2021060327A1

Cited By

  • Positive plate for lead-acid storage battery

    CN120388988A

  • Positive plate for lead-acid battery

    CN120388988B

  • Negative plate for lead-acid storage battery

    CN120388989A

  • A negative plate for a lead-acid battery

    CN120388989B